Thrombocytopenia in Healthy Term Infants: Incidence and Clinical Outcomes at Middlemore Hospital, New Zealand - Vela, Galama (Auckland University of Technology, 2019)
Neonatal alloimmune thrombocytopenia (NAIT) is caused by the destruction of an infant’s platelets by maternal allo-antibodies developed in utero against paternally acquired antigens on the foetus’ platelets. It can be associated with considerable morbidity and mortality. The incidence of NAIT is unknown in New Zealand and therefore considered uncommon and probably under-diagnosed. This study was initially designed to determine the incidence of NAIT in infants born at Middlemore Hospital, in a period of 11 years. However, it was not possible to determine the incidence from the beginning considering the definition of incidence therefore prevalence was used instead. The objectives of the study are to determine the prevalence of thrombocytopenia in otherwise healthy term infants of varying ethnicities; investigate associations of thrombocytopenic infants with clinical outcomes in affected infants and subsequent siblings and develop a suggested guideline for future detection, management of NAIT in New Zealand and Identify cases of NAIT in asymptomatic infants. This retrospective study involved analysis of 66910 cord blood full blood count (FBC) results from babies born at Middlemore Hospital between 2005 and mid – 2016. All babies with a platelet count below the reference range (150x 109/L) were selected. Relevant clinical data were collected from the clinical records of these babies and mothers. Of the total number of cord blood FBC analysed, 1.2% showed thrombocytopenia. Of these, 80.7% were term babies and the rest were preterm. Amongst these thrombocytopenic infants, 67% had no abnormal clinical features suggestive of thrombocytopenia. These asymptomatic infants were mostly term babies, the majority of whom were not followed up with repeat counts, except one, who returned with symptomatic thrombocytopenia 5 days after discharge. This infant was later diagnosed with NAIT. Investigations of family history of almost all asymptomatic thrombocytopenic infants (n = 532) examined reported that 1.9% of the mothers had one or more stillbirths, and 20.5% had experienced miscarriages. None of these mothers however, appeared to have had any association with NAIT, nor cases of intracranial haemorrhage (ICH). Furthermore, while sixteen infants (4.9%) had siblings with documented thrombocytopenia, none were attributed to NAIT. One third of the infants who were thrombocytopenic at birth were admitted for a variety of medical indications. Amongst these indications, 10 cases (0.0006% of the total number of cord blood FBC) were attributed to NAIT, of which only 3 were confirmed serologically. It can be concluded from this study that NAIT is quite uncommon in this setting despite the large number of term infants born with thrombocytopenia. It is therefore suggested that the cut off range for thrombocytopenia in cord blood in this setting must be reviewed.
Keywords: Thrombocytopenia; Intracranial haemorrhage; Neonatal alloimmune thrombocytopenia; Platelets